(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2015)
Date palm (Phoenix dactylifera L.) is harvested for its sweet fruit mainly in the middle east and other parts of the world. It has been cultivated for several thousand years and is known to be found in Mesopotamia as well. Besides the fruit, the various parts of the tree are employed for variety of uses. The stalks of the fruit, which connect the fruit to the spikelet, are very beautiful, colourful flower like structures, which have never been described earlier. These fruit stalks could be used for decorations in houses and would then add to more economic gain to the farmer. We observed these stalks and describe here this interesting finding hitherto unreported in the world literature. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22649 Int. J. Agril. Res. Innov. & Tech. 4 (2): 53-54, December, 2014